Kepemimpinan Transformatif: Meneladani Kehidupan dan Pelayanan Elia - Debi Silvia Dinata; Sandro Apriedo; Listia Septiana; Sarmauli Sarmauli (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to describe the principle of perseverance taught by Elijah through his exemplary life, explain Elijah's strategies in facing life's challenges, and identify the meaning of Elijah's faith and its relevance to everyday life. Elijah demonstrated extraordinary perseverance in his obedience to God, as seen in his story in 1 Kings 17:1-6. He remained faithful to the mission given by God, despite facing various challenges, including spiritual conflict, physical threats, social isolation, and inner turmoil. The pinnacle of Elijah's faith is seen in his confrontation with the prophets of Baal on Mount Carmel, where Elijah challenged idol worship with a strong conviction in God's power. Elijah's experience teaches the importance of maintaining faith in the midst of challenges, consistency in pursuing goals, and nurturing a personal relationship with God as a source of strength. Elijah's life also has relevance in the modern context, especially in terms of empowering leadership, spiritual integrity, moral courage, and commitment to divine truth..